TERAPI BEKAM UNTUK MENGATASI DISMENOR PADA GEN Z TANPA OBAT DI SMA N 1 GADING REJO - Khoiriyah, Isna Lailatul; Hida Damayana; Nafisah Nisrina; Yolanda Alfina Putri; Annisa Nabila Inayah; Andryan Mahendra; M. Adius Rafli; Rico Santri; Desmi Trisna Sari; Haswane Dadeh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Introduction: Dysmenorrhea, also known as menstrual pain, is a condition that frequently affects adolescent girls and can reduce learning activities and quality of life. One non-pharmacological alternative for dysmenorrhea is cupping therapy, a method of removing static blood which functions to reduce the amount of prostaglandins caused by pain while also improving blood circulation. Objective: The purpose of this activity was to enhance the knowledge and understanding of students at SMA Negeri 1 Gading Rejo regarding the utilization of cupping therapy as a natural effort in treating menstrual pain. Methods: In November 2025, the instruction was conducted using interactive lectures and educational videos, interactive Q&A sessions, and demonstrations of cupping points related to the management of dysmenorrhea. The total number of activity participants was 36 students. Results: After the activity was carried out, there was an increase in the participants' understanding of cupping care, with 65% reporting a significant increase in understanding. Participants demonstrated a high level of enthusiasm through questions and material analysis. Furthermore, they understood the procedures, benefits, and appropriate duration of the treatment. Conclusion: The educational activity on cupping therapy had a positive impact on the knowledge and skills of SMA Negeri 1 Gading Rejo students in promoting reproductive health. Cupping therapy can be considered a safe and effective non-pharmacological alternative for reducing menstrual pain in adolescents.